Active Fractions of Methanol Crude Obtained from Acacia seyal gum: Antioxidant Capacity using FTIR Analysis - Ahmed A M Elnour; Mohamed Elwathig Saeed Mirghani; Nassereldeen A Kabbashi; Md Zahangir Alam; Khalid Hamid Musa (Borneo Journal of Pharmacy, 2019)
The present study is on Acacia seyal gum (ASG), which is an exudate from Talha tree. It provides a rich source of polyphenolics compounds that are used traditionally in folk medicine. The study aims to determine the antioxidant capacity (AC) and functional groups of ASG and Prebio-T-commercial (PTC) samples. The methanol crude extracts of both ASG and PTC have fractioned into chloroform (CHF), hexane (HF), acetone (AF) and methanol (MF) using solvent-solvent portion. Both ferric reducing antioxidant power (FRAP), and cupric reducing antioxidant capacity (CUPRAC) assays for each fraction examined. Crude methanol extracts (CME) and its active compositions also analysed carefully using Fourier Transform Infrared Spectroscopy (FTIR) technique. The findings presented a wide variety of functional groups provided by the FTIR spectra (eights bands approximately. Regarding cupric reducing antioxidant capacity (CUPRAC), the methanol crude extracts values are 888.6±4.57 mg TE/100g extract, for PTC as compared to 474.3± 2.23 mg TE/100g of extract for ASG. However, both methanol and acetone fractions revealed significantly (p ≤ 0.05) high FRAP values ranged between 599.8±7.5 and 741.8±5.8 mg TE/100g fraction; for PTC and ASG, respectively. While CUPRAC showed insignificant (p ≥ 0.05) same values 356.1±2.62 mg TE/100g of fraction; for MF of both PTC and ASG respectively. Therefore, in this study, methanolic fractions (MFs) are found to be more effective than acetone fractions (AFs), except for CHF and HF. Finally, the antioxidant activity of the active fraction has provided some evidence regarding its functional groups which may have used in traditional medicine.